Peptidoglycan amidation of Staphylococcus aureus and bacteria cell physiology - Cavaco, Gonçalo Francisco Cordeiro (2018)
Peptidoglycan is a highly dynamic macromolecule that undergoes several secondary modifications during its biosynthesis. The MurT-GatD enzymatic complex is necessary for the amidation of glutamate of the stem peptide of Staphylococcus aureus peptidoglycan. This secondary modification influences critical processes of S. aureus, such as growth rate, beta-lactam and lysozyme resistance. However, the mechanisms through which it influences S. aureus physiology remain unknown. In this study, several MRSA strains and respective murT-gatD mutants were used. Since peptidoglycan is a surface-exposed macromolecule, we analyzed the influence of peptidoglycan amidation on the modulation of the cell envelope, by measuring the surface charge, through a cytochrome C association based method. For all strains, peptidoglycan amidation was associated with a more positive surface charge. Consequently, such impact could alter cell-cell aggregation and surface-adhesion properties. Overall, amidation mutants showed either increased biofilm production or formation of cell aggregates during planktonic growth; these two distinct phenotypes seemed to be associated with the biofilm matrix composition of the parental strain. In fact, amidation mutants of PIA-positive parental strains showed formation of cell aggregates, whereas the ones of PIA-negative parental strains showed higher biofilm production. Additionally, biofilm detaching assays showed that the composition of the biofilm matrix is altered in response to lack of peptidoglycan amidation. Peptidoglycan amidation was proposed to influence autolysis, by disturbing the balance between the cell wall synthetic and hydrolytic machineries and/or by acting as a signal to regulate the activity of autolysins. Zymographic assays suggested that nonamidated peptidoglycan is a better substrate for autolysins. Moreover, these enzymes seemed to be less expressed/active in amidation mutants. Western Blot and promoter fusion assays confirmed that peptidoglycan amidation influences the autolytic system, as non-amidated mutants showed lower expression of ATL and SLEI autolysins.